Prospective Teachers' Perspective on the Role of Instructor in Fostering Their Mathematical Disposition - Thesa Kandaga; Rizky Rosjanuardi; Dadang Juandi (Jurnal Elemen, 2021)
Continuous treatment is needed in developing mathematical dispositions. Even at the higher education level, some prospective teachers still need proper treatment in developing their mathematical dispositions. This study tries to reveal instructors' role in fostering their students' mathematical disposition to better didactical situations. This study is qualitative research with a content analysis approach. The results obtained in this study indicate that the instructor's role is still needed in the classroom regardless of the students' mathematical disposition. Instructors ' expected learning role becomes diverse based on the mathematical disposition grouping between good, moderate, and less mathematical dispositions. For prospective teachers who have an excellent mathematical disposition, the instructor's role is to confirm a theorem, confirm answers to questions, and the benefits of contextual topics. For prospective teachers who have a satisfactory mathematical disposition, the instructor's role is to motivate, direct the learning, and keep the classroom conductivity. Whereas for prospective teachers deficient in mathematical disposition, the instructor's role is needed as a direct learning source, structured learning director, and an enjoyable learning rhythm.